SELF-ESTEEM DEVELOPMENT OF VOCATIONAL HIGH SCHOOL STUDENTS IN INDONESIA: DOES GROUP COUNSELING WITH ASSERTIVE TRAINING TECHNIQUE HELP? - Nandang Rusmana; Anne Hafina; Riesa Rismawati Siddik; Lutfi Nur (LPMPP Universitas Negeri Yogyakarta, 2020)
Self-esteem contributes to an individual’s mental health and quality of life because it determines who they are, activities they do, as well as their personality. This study aimed to describe the development of students’ self-esteem through group counselling intervention with an assertive training technique. Employing a true experimental method with the pretest–posttest control group design, this study involved 191 students as the samples following Isaac and Michael at an error level of 5% of the total population of 420 students. From the self-esteem questionnaires, it was found that 28 students belonged to the low self-esteem group. Then, interventions were carried out in six sessions outside of class hours, with a duration of 90 minutes for each session. The data were obtained through the Coopersmith Self-Esteem Inventory (CSEI) instrument with a reliability value of .92, and analyzed using the Mann-Whitney two mean discrimination test. The results showed that students who were given group-counselling interventions with assertive training technique were better than those in the control group. Therefore, assertive training technique helps restore students' awareness of their rights to have a happy and esteemed life. Besides, assertive training technique helps renew students' confidence in the functioning of their minds and belief in their abilities in facing life challenges.